2021
DOI: 10.3390/biomedicines9101474
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Characterization of Postmolar Gestational Choriocarcinoma

Abstract: The human placenta shares properties with solid tumors, such as rapid growth, tissue invasion, cell migration, angiogenesis, and immune evasion. However, the mechanisms that drive the evolution from premalignant proliferative placental diseases—called hydatidiform moles—to their malignant counterparts, gestational choriocarcinoma, as well as the factors underlying the increased aggressiveness of choriocarcinoma arising after term delivery compared to those developing from hydatidiform moles, are unknown. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Of importance, several genes inhibited by ERBB2/ERBB3 [ 75 ] were downregulated in choriocarcinoma, among which ADAM19 ( Disintegrin And Metalloproteinase Domain-Containing Protein 19), FN1 (fibronectin 1), and FSTL3 (Follistatin Like 3) are involved in cell–cell and cell–matrix interactions and may impact cell adhesion during chorio-carcinogenesis. Interestingly, another growth factor (transforming growth factor-β1) pathway was strongly implicated in the pathogenesis and progression of GTDs [ 76 , 77 ], which suggests that disturbed growth factor signaling downstream of epigenetic changes may be in the center of disease in choriocarcinomas. In addition, ‘JAK-STAT signaling’, which is key for the cytokine- and growth factor-mediated modulation of cell proliferation and migration, was also found to be changed only in choriocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, several genes inhibited by ERBB2/ERBB3 [ 75 ] were downregulated in choriocarcinoma, among which ADAM19 ( Disintegrin And Metalloproteinase Domain-Containing Protein 19), FN1 (fibronectin 1), and FSTL3 (Follistatin Like 3) are involved in cell–cell and cell–matrix interactions and may impact cell adhesion during chorio-carcinogenesis. Interestingly, another growth factor (transforming growth factor-β1) pathway was strongly implicated in the pathogenesis and progression of GTDs [ 76 , 77 ], which suggests that disturbed growth factor signaling downstream of epigenetic changes may be in the center of disease in choriocarcinomas. In addition, ‘JAK-STAT signaling’, which is key for the cytokine- and growth factor-mediated modulation of cell proliferation and migration, was also found to be changed only in choriocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…More often, CC may also develop after normal delivery. The incidence of this type of CC is 1 per 67,000 live births [ 19 , 63 ]. Recent studies have shown that 50% of patients with recurrent HM have mutations in the gene nlrp7 [ 62 ].…”
Section: Nlrs and Cancermentioning
confidence: 99%
“…Several have demonstrated that superficial invasion of EVT is observed in the pathology of preeclampsia and fetal growth restriction (FGR) [ 10 , 11 , 12 , 13 , 14 ], while excessive invasion of the maternal decidua and myometrium by these cells is observed in gestational trophoblastic diseases (GTD) [ 15 , 16 ]. GTDs are a rare subset of placental conditions encompassing benign proliferations called partial (PHM) or complete hydatidiform moles (CHM), and their invasive counterpart named gestational trophoblastic neoplasia (GTN), of which choriocarcinoma (CC) is the most aggressive [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Mechanismen, die zum Übergang von einer Blasenmole als proliferativer, benigner Erkrankung der Plazenta zu einem Chorionkarzinom führen, sind jedoch ebenso unklar wie die Gründe für die hohe Aggressivität des postpartal auftretenden Chorionkarzinoms, verglichen mit aus einer Blasenmole entstandenen Chorionkarzinomen [6]. Die Laboruntersuchung zeigte neben einer schweren Anämie mit einem Hämoglobinspiegel von 4,8 mg/dl sowie Hämatokrit von 18,5 % auch eine Thrombozytopenie mit Thrombozyten von 86000/μl sowie Leukozyten von 10,4*10 3 /nl.…”
Section: Introductionunclassified